SEROEPIDEMIOLOGY OF TOXOPLASMA, RUBELLA, CYTOMEGALOVIRUS AND HERPES SIMPLEX VIRUS -2 IN WOMEN WITH BAD OBSTETRIC HISTORY. PART I: TOXOPLASMA AND RUBELLA INFECTIONS - Abdulghani Mohamed Alsamarai; Zainab Khalil Mohamed Aljumaili (Our Dermatology Online, 2013)
Bad obstetric history (BOH) is associated with social and psychological impacts on society worldwide. The causes of BOH may be genetic, hormonal, abnormal maternal immune response, and maternal infection. In women with bad obstetric history (BOH), Toxoplasma (T) IgG high rate has been reported for Nepal (55.2%), while high (42.5%) and lowest (6.97%) active toxoplasma infections has been reported for India. In Arab countries, IgG and IgM higher and lowest seroprevalence rates were for Iraq. The higher susceptibility rates for Rubella in Arab countries excluding Iraq were reported in Morocco (83.4%), Sudan (34.7%), Qatar (25.1%), and Tunisia (20.3%). The lowest susceptibility was reported for Saudi Arabia (6.7%). In Iraq, studies indicate a high susceptibility rates in Thi Qar (98.05%), Kirkuk (91%), Baghdad (79%), and Waset (45.7%). The lowest susceptibility rates were reported for Diyala (0%) in women with previous abortion, and 3.9% in pregnant women without history of BOH.